2021
DOI: 10.1177/15269248211002793
|View full text |Cite
|
Sign up to set email alerts
|

Life Expectancy after Liver Transplantation for Non-Cirrhotic Hepatocellular Carcinoma

Abstract: Background: Hepatocelluar carcinoma typically occurs with underlying cirrhosis. However roughly 20% of cases arise in a non-cirrhotic liver. There is limited literature that addresses the long-term survival of the narrow subgroup who received transplantation. For such patients we sought to calculate life expectancies both at time of transplant and several years later, stratified by key risk factors, and to determine if survival has improved in recent years. Such information can be helpful in making treatment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
4
1
Order By: Relevance
“…The life expectancies given here for NASH patients were modestly higher than those given in prior studies on life expectancy after transplant for HCC 16,17 or alcohol related liver disease (ALD). 18 For example, for males aged 40 we report 20 years, while the three prior studies indicated 16 (HCC with cirrhosis), 15 (HCC without cirrhosis), and 17 (ALD), respectively.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The life expectancies given here for NASH patients were modestly higher than those given in prior studies on life expectancy after transplant for HCC 16,17 or alcohol related liver disease (ALD). 18 For example, for males aged 40 we report 20 years, while the three prior studies indicated 16 (HCC with cirrhosis), 15 (HCC without cirrhosis), and 17 (ALD), respectively.…”
Section: Discussioncontrasting
confidence: 64%
“…Secondly, among the 557 (9%) of patients who were of normal weight (body mass index (BMI) 18-25), we found that 5 were underweight when placed on the transplant registration, 18 were overweight, and the remaining 534 were of normal weight. Thirdly, the 5% of patients with HCC were found to have lower MELD scores than the overall group (for example, 26% had scores 6-10% and 39% had scores [11][12][13][14][15][16][17][18], though this finding should be viewed with caution as 47% of patients had missing information with respect to the presence of HCC. Fourthly, there were too few patients of other races (12% Hispanic, 2% Black) to report results separately by race, and indeed a detailed study of the effect of race is outside the scope of the present work.…”
Section: Resultsmentioning
confidence: 99%
“…The life expectancies given here for ALD patients are similar to those given in two prior studies on life expectancy after transplant for HCC. 19,20 For example, for males aged 40 we report 17 years, while the two prior studies indicated 15 (HCC with cirrhosis), and 16 (NC-HCC), respectively.…”
Section: Discussionmentioning
confidence: 95%
“…The methods are similar to our work in two prior studies. 19,20 We identified and followed a cohort of ALD liver transplant patients in the United States to identify factors related to survival and to calculate life expectancies for various subgroups. We used standard methods of survival analysis and life table construction.…”
Section: Design/methodsmentioning
confidence: 99%
See 1 more Smart Citation